Spatio-temporal structure of an earthworm community and soil heterogeneity in a tropical pasture (Carimagua, Colombia) - Decaëns, Thibaud; Rossi, J.P. (International Center for Tropical Agriculture, 2001)
Only a small part of the spatio-temporal structures of earthworm distribution was correlated with soil properties. Small species were more abundant in patches were soil was more compact, while large species were associated with high root biomass and total C levels. The question whether earthworm spatiotemporal distribution induces similar patterns in soil properties or the contrary occurs is discussed. Our results suggest that earthworm community organization mostly corresponds to a non-equilibrium system where mobile earthworm populations influence soil properties. The overall effect of earthworm community on soil is difficult to assess due to the predominance of factors that preferentially express themselves at large scales in the ecological hierarchy.